A multi-centre, prospective epidemiological surveillance study considering ophthalmic complications of functional endoscopic sinus surgery. Issue 3 (9th March 2020) - Burgess, S; Foulds, J; White, P; Foot, B; MacEwen, C
Abstract: Objectives: This prospective, epidemiological British Ophthalmological Surveillance Unit study into ophthalmic complications of functional endoscopic sinus surgery aimed to determine the minimum incidence, presenting features and management throughout the UK. Methods: Cases of ophthalmic complications of functional endoscopic sinus surgery, between February 2016 and February 2018, were identified through the British Ophthalmological Surveillance Unit reporting card system. Reporting ophthalmic consultants were sent an initial questionnaire, followed by a second questionnaire at six months. Results: Twenty-six cases of ophthalmic complications of functional endoscopic sinus surgery were reported. The majority (16 cases (62 per cent)) had limitations of ocular motility at presentation. The most common final diagnosis was rectus muscle (33 per cent) and nasolacrimal duct trauma (27 per cent). Using national data, this study reports a minimum incidence of ophthalmic complications of functional endoscopic sinus surgery in the UK of 0.2 per cent over two years. Conclusion: In terms of ophthalmic complications, functional endoscopic sinus surgery is shown to be safe. Ophthalmic complications are rare, but when they do occur, they commonly result in rectus muscle trauma, often requiring surgical intervention.